Impact of Adopting Diesel-CNG Dual-Fuel Engine on Haulage - Towoju, Olumide Adewole (International Journal of Sustainable Energy and Environmental Research, 2022)
Climate change brought about by the emission of Greenhouse Gases (GHG) has shone a spotlight on the role of the internal combustion engine. These engines are significant contributors to GHG emissions. However, there have been recent improvements in their design. Natural gas produces lower GHG emissions during combustion, making it suitable as a fuel in internal combustion engines. Aside from the emission impact of gasoline and diesel, the collapse of Nigeria’s petroleum refineries has impacted the availability of the products and caused them to have exorbitant prices for the populace. The country is, however, richly blessed with natural gas, which is waiting to be tapped and put to use. The conversion of a fleet of diesel trucks by a local haulage company will have both financial and GHG emissions impacts. This study investigates these impacts. By the fifty-third month, the investment starts to yield dividends, which accrue to over 34,000 over the useful life of each truck. Also, for each converted truck there is a reduction in GHG emissions of around 13.22 tons annually.